Experts’ Opinions on Iraq’s Readiness to Confront Dust Storms in Light of Climate Change (Journal of the College of Basic Education, 2026)
The study aimed to identify experts’ opinions on the level of Iraq’s readiness to dust storms in light of climate change, focusing on national plans and strategies, technical and institutional capacities, as well as obstacles and challenges affecting this readiness. The descriptive survey method was adopted. The study population consisted of geography experts at the University of Baghdad, and the sample included (185) male and female experts selected according to the gender variable. A questionnaire consisting of three main domains was developed to achieve the objectives of the study. The results indicated that national plans and strategies are achieved at a good level, and that there is a relatively high level of technical and institutional capacities. However, experts showed a high awareness of the existence of significant obstacles and challenges affecting Iraq’s readiness, most notably limited funding, lack of modern technologies, and weak institutional coordination. The study concluded with the need to enhance integration between national planning and technical capacities and to address existing challenges in order to improve Iraq’s readiness to confront dust storms under climate change conditions.